2022
DOI: 10.1186/s12913-022-08359-7
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of irrational use of antibiotics among children: a mixed-method study among prescribers and dispensers in Tanzania

Abstract: Background Misuse of antibiotics has been associated with poor knowledge, attitude and practice (KAP). Therefore, this study aimed to assess if KAP of prescribers and dispensers could drive irrational use of antibiotics among children in Tanzania. Methods A convergent parallel mixed-methods study design that employed quantitative and qualitative approaches was conducted in 14 regional referral hospitals (RRHs). A total of 108 participants, prescrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…It is known that successful implementation of stewardship activities requires unwavering commitment from senior leadership, 33 to ensure evidence-based treatment, proper planning to avoid expiry of medications, accessibility of the required stock of antimicrobials, establishment of hospital therapeutic committees and conducting of regular audits of antibiotic use, all of which are requirements of ASP activities as per NAPAR. 17 Like other studies, 22,34 findings from this study support the notion that implementation of an ASP without the commitment of senior leadership is likely to fail.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It is known that successful implementation of stewardship activities requires unwavering commitment from senior leadership, 33 to ensure evidence-based treatment, proper planning to avoid expiry of medications, accessibility of the required stock of antimicrobials, establishment of hospital therapeutic committees and conducting of regular audits of antibiotic use, all of which are requirements of ASP activities as per NAPAR. 17 Like other studies, 22,34 findings from this study support the notion that implementation of an ASP without the commitment of senior leadership is likely to fail.…”
Section: Discussionsupporting
confidence: 73%
“…The patients' rigid attitude regarding not conforming to the instructions provided by the healthcare workers is also reported elsewhere, and mass education is observed to reduce these practices. 22,38 Lastly, one of the activities to be performed in ASPs is training and capacity building of the healthcare workers, and according to the NAPAR this has been an ongoing activity since its launch in 2017. However, findings from the current study have shown limited training opportunities, in terms of who can access this training and selective CME, where most do not focus on ASP.…”
Section: Discussionmentioning
confidence: 99%
“…Patients’ attitudes and socioeconomic status also contribute to the spread of AMR [ 34 ]. Recent studies indicate that knowledge of antibiotic use and resistance could be better among Bangladeshi people.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic misuse has been categorized as both community-and healthcare-providerdriven owing to a lack of understanding and awareness of the dangers of antibiotic abuse in the community, availability of antibiotics without a prescription, and consumption of leftover medications, even though prescibers and dispensers were found to have adequate knowledge on antibiotic use [7,21]. The leftover antibiotics are available because patients are unable to complete the medication provided to them for a variety of reasons that vary from person to person, such as adverse effects, feeling better, or drug expiry [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The leftover antibiotics are available because patients are unable to complete the medication provided to them for a variety of reasons that vary from person to person, such as adverse effects, feeling better, or drug expiry [22,23]. Predictors of antibiotic misuse among healthcare providers include pharmacists' and prescribers' knowledge, attitude, and practice, patient/doctor contact, a lack of rapid diagnostic tests, pharmaceutical promotion, and a lack of adequate antibiotic education for healthcare professionals [7,21].…”
Section: Introductionmentioning
confidence: 99%